The Modern Methods in the Surgical Reconstruction and Rehabilitation of the Orofacial Region: A Review of the Literature - Ó’Fearraigh, Pádraig (Trinity Student Medical Journal, 2008)
Maxillofacial and dental defects often cause detrimental effects to patient health and appearance. A holistic approach of restoring lost dentition along with bone and soft tissue is now the standard treatment of these defects. Recent improvements in reconstructive techniques over the past number of decades especially osseointegration, microvascular free tissue transfer and improvements in bone engineering have yielded excellent functional and aesthetic outcomes. This article reviews the literature on these modern reconstructive and rehabilitation techniques.